2015
DOI: 10.5935/0103-5053.20150359
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Separation of Sibutramine by Capillary Zone Electrophoresis

Abstract: The chiral separation of sibutramine enantiomers was resolved succesfully by capillary zone electrophoresis using cyclodextrins (CDs) as chiral selectors. A complex screening of several different native and derivatized, neutral and ionized cyclodextrine derivatives was performed. The effects of buffer type, concentration and pH, cyclodextrin type and concentration, applied voltage, capillary temperature and injection parameters on the chiral resolution were examined. The best results on a very short fused sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Capillary zone electrophoresis (CZE) using derivatized neutral CD -methyl-β-CD (M-β-CD) or derivatized ionized CD -carboxymethyl-β-CD as chiral (CM-β-CD) selectors was the first-choice method used in several studies for the enantioseparation of SIB enantiomers [27][28][29][30].…”
Section: Chiral Separation Of Sibutramine By Electrophoretic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillary zone electrophoresis (CZE) using derivatized neutral CD -methyl-β-CD (M-β-CD) or derivatized ionized CD -carboxymethyl-β-CD as chiral (CM-β-CD) selectors was the first-choice method used in several studies for the enantioseparation of SIB enantiomers [27][28][29][30].…”
Section: Chiral Separation Of Sibutramine By Electrophoretic Methodsmentioning
confidence: 99%
“…During the optimization process, the effects of buffer composition, background electrolyte concentration and pH, CD type and concentration, applied voltage, capillary temperature and injection parameters on the chiral resolution were studied. The best results on a short fused silica capillary of 30 cm × 50 µm were obtained using a 50 mM phosphate buffer containing 10 mM randomly methylated β-CD (RAMEB) as chiral selector at a pH of 4.50 with UV detection at 220 nm; the separation of enantiomers was achieved in approximately 5 minutes [29].…”
Section: Chiral Separation Of Sibutramine By Electrophoretic Methodsmentioning
confidence: 99%
“…Sibutramine: 2016 spectrofluorometric method for analysis of sibutramine, indapamide and hydrochlorothiazide compounds in weight-reducing tonic samples [ 442 ]; enantiomeric separation of Sibutramine by capillary zone electrophoresis using cyclodextrins as chiral selectors [ 443 ]; determination of Sibutramine in slimming food supplements by a validated HPLC-ES-MS/MS method [ 444 ]; thermal behaviors of racemic sibutramine hydrochloride monohydrate as well as that of the anhydrous state were investigated by differential scanning calorimetry (DSC) [ 445 ]; a ‘natural’ weight loss product containing sibutramine [ 446 ]; simultaneous detection of sibutramine and phenolphthalein by CE [ 447 ]; 2017 ATR-FTIR spectroscopic method to detect sibutramine in dietetic herbal foods, teas and dietary supplements [ 448 ]; identification of sibutramine using a fully integrated GC/FT-IR/MS instrument [ 449 ]; SERS method for detection of Sibutramine HCL in seven types of commercial slimming capsules [ 450 ]; 2018 continuation of Lanzarotta’s 2017 study using fully integrated GC-FT-IR-MS to identify and confirm the presence of sibutramine and AB-FUBINACA [ 451 ]; HPLC-PDA, LC-Q-TOF/MS, FT-IR, and NMR for isolation and structural characterization of a novel sibutramine analogue, chlorosipentramine, in a slimming dietary supplement [ 452 ]; LC-MS/MS (ESI) method for detecting sibutramine in herbal supplements [ 453 ]; 2019 identification of slimming agents apprehended in Brazil using FTIR, Differential Scanning Calorimetry and GC-MS including the comparison of the efficiency of solid-liquid extraction and microwave-assisted extraction [ 454 ]; portable square-wave voltammetric method for fast screening and quantification of sibutramine in herbal formulations and dietary supplements samples [ 455 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…Moreover, when M‐β‐CD was used as a CS, the complexation constants were higher for 10‐hydroxywarfarin than for warfarin, and therefore, the former exerts stronger affinity to M‐β‐CD and stronger stereoselective effect. RAMEB was used in CE as a CS for the enantioseparation of several analytes, such as omeprazole, amlodipine, and ofloxacin . Briefly, Hancu et al.…”
Section: Chiral Selectorsmentioning
confidence: 99%
“…Among all the examined CDs, RAMEB was selected as the optimum since it provided the best R S (2.48) at the shortest analysis time (<6 min). RAMEB was also used for the chiral separation of sibutramine, and the method was validated based on linearity, precision, LOD, LOQ, and intra‐ and interday reproducibility . In a recent study , molecular modeling demonstrated that RAMEB interacts with ofloxacin enantiomers mainly by Van der Waals forces, and a small difference in the binding energies of the two enantiomers was observed.…”
Section: Chiral Selectorsmentioning
confidence: 99%